Tumor-educated T regs drive organ-specific metastasis in breast cancer by impairing NK cells in the lymph node niche - Kos, Kevin; Aslam, Muhammad A; van de Ven, Rieneke; Wellenstein, Max D; Pieters, Wietske; van Weverwijk, Antoinette; Duits, Danique E M; van Pul, Kim; Hau, Cheei-Sing; Vrijland, Kim; Kaldenbach, Daphne; Raeven, Elisabeth A M; et al. (Cell reports (Cambridge), 2022)
Breast cancer is accompanied by systemic immunosuppression, which facilitates metastasis formation, but how this shapes organotropism of metastasis is poorly understood. Here, we investigate the impact of mammary tumorigenesis on regulatory T cells (T ) in distant organs and how this affects multi-organ metastatic disease. Using a preclinical mouse mammary tumor model that recapitulates human metastatic breast cancer, we observe systemic accumulation of activated, highly immunosuppressive T during primary tumor growth. Tumor-educated T show tissue-specific transcriptional rewiring in response to mammary tumorigenesis. This has functional consequences for organotropism of metastasis, as T depletion reduces metastasis to tumor-draining lymph nodes, but not to lungs. Mechanistically, we find that T control natural killer (NK) cell activation in lymph nodes, thereby facilitating lymph node metastasis. In line, an increased T /NK cell ratio is observed in sentinel lymph nodes of breast cancer patients compared with healthy controls. This study highlights that immune regulation of metastatic disease is highly organ dependent.